El educador como investigador de su práctica pedagógica: la importancia de la reflexión en la educación para la salud (2010)
ABSTRACT: To present the process and results of an action research in the educational dimension, the growth and development program of a health institution in Medellin. Methodology: following Stenhouse’s ideas about a teacherresearcher, it was developed a reflective process where the program’s teams, researched their pedagogical practices, and analyzed them taking in consideration their own experience as well as theory coming from past research done in their institution, and the scientific literature. Results: through a reflective process and by investigating their pedagogical process, educators were able to design the program from a wider perspective: child rearing. Also they were able to locate themselves in a different way with respect to education and to parents generating alternative proposal for education Discussion: research experience shows the difficulty of making changes in pedagogical perspectives in health education, usually based on traditional or behavioral models. According to the results, this research proposal is presented as a way to forward in the strengthening of a educational dimension in health field from an alternative perspective.